BASICS OF EDUCATIONAL MANAGEMENT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Management of the pedagogical activity of the educational institution meaning planning, organization, stimulation, control and analysis of the pedagogical process. The theory of management of educational institutions was enriched with the theory of management of educational institutions. Management theory is characterized by trust in employees, creating conditions for their productive work and mutual respect.